An exploratory prospective study of the association between communication skills and employment outcomes after severe traumatic brain injury. (July 2013) - Rietdijk, Rachael; Simpson, Grahame; Togher, Leanne; Power, Emma; Gillett, Lauren
Abstract Primary objective: The aim of this pilot study was to explore possible correlations between measures of functional communication skills in the first year post-injury and later employment outcome. Design: A preliminary observational study employing a prospective longitudinal design. Methods: Fourteen adults with traumatic brain injury completed an assessment involving two functional communication measures: an objective test of cognitive communication skills (Functional Assessment of Verbal Reasoning and Executive Strategies, FAVRES) and self-ratings of communication impairment (LaTrobe Communication Questionnaire, LCQ). Follow-up of participants' employment outcome was conducted 9–18 months after the initial assessment. Results: At follow-up, eight participants had returned to employment (working a similar number of hours to their pre-injury status), five were unemployed and one was lost to follow-up. Employment status at follow-up was strongly correlated with both FAVRES Total Accuracy scores (r = 0.833) and Total Rationale scores (r = 0.837), but there were no correlations with FAVRES Time and Reasoning scores or with the LCQ. Conclusions: The FAVRES shows initial promise as an assessment that may be associated with successful employment outcome following traumatic brain injury. Further research with larger samples is required to provide further information on the prognostic utility of measures such as the FAVRES and the LCQ.